Remission of alcohol dependency following deep brain stimulation of the nucleus accumbens: valuable therapeutic implications?. Issue 10 (18th September 2007) - Kuhn, Jens; Lenartz, Doris; Huff, Wolfgang; Lee, SunHee; Koulousakis, Athanasios; Klosterkoetter, Joachim; Sturm, Volker
Abstract : Chronic consumption of alcohol represents one of the greatest health and socioeconomic problems worldwide. We report on a 54-year-old patient with a severe anxiety disorder and secondary depressive disorder in whom bilateral deep brain stimulation (DBS) of the nucleus accumbens was carried out. Despite the absence of desired improvement in his primary disorder, we observed a remarkable although not primarily intended alleviation of the patient's comorbid alcohol dependency. Our case report demonstrates the extremely effective treatment of alcohol dependency by means of DBS of the nucleus accumbens and may reveal new prospects in overcoming therapy resistance in dependencies in general.